Wyniki leczenia siatkówczaka – chemioterapia skojarzona z leczeniem miejscowym - Kobylarz, Joanna; Piwowarczyk, Anna; Romanowska-Dixon, Bożena; Balwierz, Walentyna; Dłużniewska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: Of this study was to evaluate the results of combined treatment for intraocular retinoblastoma. Materials and methods: We examined 23 children (32 eyes), 14 with unilateral and 9 with bilateral disease. 53% of eyes had the stage V of the disease, according to Reese – Ellsworth. Results: In I-III group according to R-E, it was possible to save more than 90% of eyes. In group IV-V we saved 20% of eyes. Conclusions: Chemoreduction combined with local treatment is an optimal method of treatment for retinoblastoma, especially in I-III group.